Upregulation of Tissue and Urinary Nicotinamide N-Methyltransferase in Bladder Cancer: Potential for the Development of a Urine-Based Diagnostic Test - Sartini, Davide; Muzzonigro, Giovanni; Milanese, Giulio; Pozzi, Valentina; Vici, Alexia; Morganti, Stefano; Rossi, Valentina; Mazzucchelli, Roberta; Montironi, Rodolfo; Emanuelli, Monica (Cell biochemistry and biophysics, 2013)
Carcinoma of the bladder is one of the most common urologic malignancies occurring worldwide. Diagnosis and monitoring of bladder urothelial carcinoma (UC) are based on cystoscopy and urinary cytology. However, these diagnostic methods still have some limitations, mainly related to invasive nature and lack of sensitivity. New reliable and non-invasive biomarkers for bladder cancer detection are therefore required. To explore the involvement of enzymes of drug metabolism in bladder cancer, in the present study, we analyzed the gene expression profiles of tumor and normal looking tissues obtained from the same patient by cDNA macroarray. The enzyme nicotinamide N -methyltransferase (NNMT) was identified as a highly expressed gene in bladder cancer. RT-PCR, Real-Time PCR, Western blot analysis, and catalytic activity assay, performed on a large cohort of patients with bladder UC, confirmed NNMT upregulation. NNMT mRNA and protein levels were also determined in urine specimens obtained from patients with bladder UC and healthy subjects. We found that NNMT expression levels were significantly higher in patients with bladder tumor compared to controls that showed very low or undetectable amounts of NNMT transcript and protein. Our results indicate that a marked NNMT increase is a peculiar feature of bladder UC and suggest the potential suitability of urine NNMT expression levels determination for early and non-invasive diagnosis of bladder cancer.